ISLAMIC EXCLUSIVISM: Perspectives on the Lembaga Dakwah Islam Indonesia (LDII) Sect and the PKS Tarbiyah Group from a Postcolonial Lens: EKLUSIVISME ISLAM: Pandangan terhadap Sekte Lembaga Dakwah Islam Indonesia (LDII) dan Kelompok Tarbiyah PKS Perspektif Pascakolonial - yudha, Gesit; Syahril Ramadhan; Maulana Bagus Rahmat (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
This research is motivated by the strengthening of Islamic exclusivism in Indonesia which is not only derived from theological differences, but also from power relations in postcolonial societies. Certain groups are often positioned as subalterns, namely those who are marginalized in the dominant discourse. This study aims to analyze the construction of Islamic exclusivism through hegemonic relations and the position of the Indonesian Islamic Da'wah Institute (LDII) and the Tarbiyah network of the Prosperous Justice Party (PKS) in religious and political discourse. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with five informants, literature studies, and analysis of post-reform religious-political discourse. The analysis was conducted from a postcolonial perspective and using subaltern concepts to identify patterns of dominance and resistance. The results of the study show that Islamic exclusivism is a construction of hegemonic power relations. LDII is marginalized through the stigma of being a deviant group, while PKS, although electorally strong, still experiences marginalization in the socio-cultural realm due to the label of political Islam. Both negotiated identities to gain legitimacy. These findings provide a new understanding that the phenomenon of exclusivism is not only rooted in theological issues, but is also a result of social and political constructions that place certain groups in a subaltern position.